Apakah Pelatihan dan Lingkungan Kerja Fisik Berpengaruh terhadap Kinerja Pegawai? - Salma D; Anisah; Siti Nurmin (Syntax Corporation, 2023)
Government organizations have come under public scrutiny due to the perceived underperformance of their employees. It is suspected that factors influencing this issue are training and the physical working environment. Therefore, this research aims to examine and analyze whether Training and the Physical Working Environment indeed have an impact on Employee Performance at the Regional Library and Archives Office of Morowali Regency. The study involved 30 respondents and adopted a quantitative research approach. Literature review, interviews, and questionnaires were employed as data collection methods. The data analysis technique used to address the research questions was multiple linear regression using the SPSS software. The results of this research indicate that Training and the Physical Working Environment, both simultaneously and partially, have a positive yet non-significant influence on Employee Performance at the Regional Library and Archives Office of Morowali Regency.